Trading with National Currency: Is the Turkish Lira Stable? - Bakr, Ayman M. (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to study the stability of using national currencies for trading between Turkey and its partners in order to mitigate the risks of exchange rate volatility. We have employed wavelet coherence technique to data extracted for the Turkish lira against the currencies of its major trade partners: Germany, Russia, China, Italy, and UK. The time series cover the period from March 1996 to October 2019. Our findings show that the Turkish lira exchange rate with the German, Russian, Italian, and UK currency pairs is stable in the long-term. The exchange rate between the Turkish lira and the Chinese yuan needs further studying before a decision can be taken. The findings have important implications for policymakers and traders.